Synthesis, Activity, and Docking Study of Novel Phenylthiazole‐Carboxamido Acid Derivatives as FFA2 Agonists. (15th February 2016) - Ma, Liang; Wang, Taijin; Shi, Min; Fu, Ping; Pei, Heying; Ye, Haoyu
Abstract : Free fatty acid receptor 2 (FFA2), also known as GPR43, is activated by short‐chain fatty acids (SCFAs) that are mainly produced by the gut microbiota through the fermentation of undigested carbohydrates and dietary fibers. FFA2 currently appears to be a potential target in the management of obesity, diabetes, inflammatory diseases, and cancer. In the study, a series of novel phenylthiazole‐carboxamido acid derivatives has been synthesized and evaluated as potential orthosteric FFA2 ligands for the study of structure–activity relationships. Compound6e was found to exhibit the twofold potent agonistic activity in the stable hFFA2‐transfected CHO‐K1 cells (EC50 = 23.1 μ m ) as that of positive control propionate (EC50 = 43.3 μ m ). We also reported the results of mutagenesis studies based on the crystal structure of hFFA1 bound to TAK‐875 at 2.3 Å resolution to identify important residues for orthosteric agonist6e inducing FFA2 activation. Abstract : Novel phenylthiazole‐carboxamido acid derivatives have been synthesized and evaluated as potential FFA2 ligands for the study of structure‐activity relationship. Compound 6e was found to exhibit two‐fold potent agonistic activity (EC50=23.1 ?M) as that of positive control Propionate (EC50=43.3 ?M) in the stable hFFA2‐transfected CHO‐K1 cells. Mutagenesis studies identified important residues for orthosteric agonist 6e inducing FFA2 activation.